Varied Mechanisms and Models for the Varying Mitochondrial Bottleneck - Johnston, Iain G. (Frontiers in Cell and Developmental Biology, 2019)
Mitochondrial DNA (mtDNA) molecules exist in populations within cells, and may carry mutations. Different cells within an organism, and organisms within a family, may have different proportions of mutant mtDNA in these cellular populations. This diversity is often thought of as arising from a ‘genetic bottleneck’. This article surveys approaches to characterise and model the generation of this genetic diversity, aiming to provide an introduction to the range of concepts involved, and to highlight some recent advances in understanding. In particular, differences between the statistical ‘genetic bottleneck’ (mutant proportion spread) and the physical mtDNA bottleneck and other cellular processes are highlighted. Particular attention is paid to the quantitative analysis of the ‘genetic bottleneck’, estimation of its magnitude from observed data, and inference of its underlying mechanisms. Evidence that the ‘genetic bottleneck’ (mutant proportion spread) varies with age, between individuals and species, and across mtDNA sequences, is described. The interpretation issues that arise from sampling errors, selection, and different quantitative definitions are also discussed.